Education Reform and Its Implication for EFL Teachers Competencies - Suwarsih Madya (TEFLIN Journal: A publication on the teaching and learning of English, 2003)
The teaching of English as a foreign language in Indonesia (abbreviated TEFLIN hereafter) takes place within the context of the national education system, which is also influenced by what happens in other major systems of which one is the political system. It follows that whatever change happens in the political system will certainly affect the education system, and whatever happens in the education system will in turn influence TEFLIN. The shift from the centralized to decentralized system of government, as stipulated in Law No. 22 of 1999, has required fundamental changes in the education system. Through an Education Bill, passed on June 11, 2003 by the Parliamnet, major changes have been proposed, with the shift from a highly centralized system to decentralized open system being the most fundamental reform. School-based management requires active participation of all stakeholders in the decision-making processes. All of these changes certainly have implications for TEFLIN in general and EFL teachers competencies in particular.